The Effect of the Penteresh and Raguloth Models on the Acquisition of Linguistic Concepts among the Second Intermediate Students and Developing Their Systemic Thinking - Salih Hussein, Falah; Salih Fayyadh, Maad (Opción, 2019)
The research was carried out in Iraq and aims to identify “the effect of the Pentere- ich and Raguloth models in acquiring the linguistic concepts of the second grade students and the development of their systemic thinking”. The sample of the research consisted of second grade students. The average num- ber of students was 60. The number of students was divided into two groups. The first experimental group studied the Penteresh model. It consisted of 20 students. The second experimental group was studied according to the Rijloth model. Of the (20) students, while the control group, which was studied in the usual way, went from (20) students. The two experimental and control tests were evaluated in a number of variables (age, achievement, intelligence). The teaching plans for the Penteresh and Reigloth models were prepared in the usual way and then the language acquisition test was prepared. All the necessary cykometric properties to adjust the scale. At the end of the experiment, the test of the system thinking skills was applied before and after a period of (21) paragraphs. After applying the test, the data were processed statistically The research reached the following result: The Pentereich and Reigluth models help to develop the systemic thinking skills of second-graders and acquire linguistic concepts. The researchers suggested that other models of structural theory should be adopted and their impact on systemic thinking skills.